A solar-driven high-strength atmospheric water-collecting composite material, preparation method and application thereof

By loading hygroscopic compounds on gel substrates of MXene, chitosan and polyacrylamide, the photothermal conversion performance of MXene solves the problem that existing gel materials need to consume energy when adsorbing water, achieving efficient water vapor adsorption and release driven by solar energy, and improving the strength and toughness of the material.

CN115975262BActive Publication Date: 2025-03-14CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211603484.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-13
Publication Date
2025-03-14
Estimated Expiration
2042-12-13

AI Technical Summary

Technical Problem

Existing gel materials need to consume energy when adsorbing water, and their strength is not ideal, difficult to set, and easy to collapse, limiting their application areas.

Method used

By loading hygroscopic compounds on gel substrates containing MXene, chitosan and polyacrylamide, solar-driven water vapor adsorption and release are achieved using MXene's photothermal conversion properties.

Benefits of technology

It realizes adsorption and release of water vapor through solar energy without energy consumption, and the material has high strength and toughness, which broadens its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115975262B_ABST
    Figure CN115975262B_ABST
Patent Text Reader

Abstract

The present invention discloses a solar-driven high-intensity atmospheric water-collecting composite material, a preparation method and application thereof, and relates to the technical field of gel materials. The solar-driven high-intensity atmospheric water-collecting composite material comprises a gel substrate, and hygroscopic compounds are loaded in the pores and surface of the gel substrate; wherein the gel substrate comprises MXene, chitosan and polyacrylamide. By loading hygroscopic compounds on a gel substrate containing MXene, chitosan and polyacrylamide, the introduced MXene can be used as a photothermal component to give the hydrogel good photothermal conversion performance, relying only on solar energy to analyze and adsorb water without consuming energy; the prepared composite hydrogel material not only has larger pores, but also has very ideal strength and toughness, which is conducive to further broadening its application field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gel materials, and in particular to a solar-driven high-strength atmospheric water-collecting composite material, a preparation method and application thereof. Background Art

[0002] Hygroscopicity refers to the ability to absorb moisture from a gaseous environment. Hygroscopic compounds can not only remove excess moisture from the environment and reduce humidity, but also absorb trace water in a dry environment, thereby fixing the moisture. It has important applications in water extraction in deserts and Gobi.

[0003] Commonly used hygroscopic compounds such as LiCl, CaCl2, etc. are used to prepare gel materials. However, the current gel materials generally have the following problems:

[0004] (1) Generally, it requires energy consumption, such as electricity, to achieve the desorption of adsorbed water, which does not meet the requirements of green environmental protection;

[0005] (2) The strength of gel materials is not ideal, they are difficult to shape, easy to collapse, and fragile, which to some extent limits their application areas.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a solar-driven high-strength atmospheric water-collecting composite material, its preparation method and application, aiming to achieve solar-driven light release while ensuring the mechanical properties of the material and expanding its application range.

[0008] The present invention is achieved in that:

[0009] In a first aspect, the present invention provides a solar-driven high-strength atmospheric water-harvesting composite material, comprising a gel substrate, wherein a hygroscopic compound is loaded in the pores and on the surface of the gel substrate;

[0010] Among them, the gel matrix contains MXene, chitosan and polyacrylamide.

[0011] In an optional embodiment, the hygroscopic compound is selected from at least one of LiCl, CaCl2, MgSO4, and CuSO4; preferably LiCl.

[0012] In an alternative embodiment, the loading amount of the hygroscopic compound is 3-5.2 g / g; preferably 3-4 g / g;

[0013] Preferably, in the gel matrix, the mass ratio of MXene, chitosan and polyacrylamide is 1:5-7:45-55; preferably 1:5.8-6.2:48-52.

[0014] In a second aspect, the present invention provides a method for preparing any one of the aforementioned embodiments of the solar-driven high-strength atmospheric water-collecting composite materials, comprising: preparing a gel substrate containing MXene, chitosan and polyacrylamide, and loading a hygroscopic compound on the gel substrate.

[0015] In an optional embodiment, the preparation process of the gel substrate includes: mixing and dissolving chitosan, MXene and acrylamide monomers, reacting at high temperature in the presence of a cross-linking agent and an initiator to form a hydrogel, swelling the hydrogel, and freeze-drying the hydrogel;

[0016] Preferably, the high temperature reaction has a reaction temperature of 60-80°C and a reaction time of 1-3 hours.

[0017] In an optional embodiment, chitosan is dissolved in an acetic acid aqueous solution to obtain a chitosan aqueous solution, the chitosan aqueous solution is mixed with a MXene dispersion to obtain a mixed solution, the mixed solution is mixed and dissolved with an acrylamide monomer, and then sequentially mixed with a cross-linking agent and an initiator and reacted at high temperature to form a hydrogel, the hydrogel is allowed to stand for 8-24 hours and then washed with water, and then the washed hydrogel is immersed in water for swelling, and freeze-dried after being frozen and fixed;

[0018] Preferably, the soaking time is 60-85 hours, and the water is replaced every 6-10 hours during the soaking process;

[0019] Preferably, the freezing setting time is 8-20 hours, and the freeze drying time is 60-85 hours.

[0020] In an optional embodiment, the concentration of MXene in the mixed solution is 1-3 mg / mL, and the mass ratio of MXene to acrylamide monomer is 1:45-55;

[0021] Preferably, when preparing the acetic acid aqueous solution, the volume fraction of acetic acid is controlled to be 2-3%, the mass fraction of chitosan in the chitosan aqueous solution is 1-3%; and the concentration of the MXene dispersion is 4-6 mg / mL.

[0022] In an optional embodiment, the crosslinking agent is selected from at least one of N,N-methylenebisacrylamide (MBA), divinylbenzene and diisocyanate;

[0023] Preferably, the initiator is selected from at least one of potassium persulfate and ammonium persulfate (APS);

[0024] Preferably, the mass ratio of the crosslinking agent to the acrylamide monomer is 0.5-0.7:100, and the mass ratio of the initiator to the acrylamide monomer is 3-5:100;

[0025] Preferably, before adding the crosslinking agent and the initiator, an inert gas is introduced into the system to remove oxygen in the system.

[0026] In an optional embodiment, the process of loading the hygroscopic compound on the gel substrate comprises: immersing the obtained gel substrate in an aqueous solution formed by the hygroscopic compound, taking it out and drying it; wherein the concentration of the aqueous solution of the hygroscopic compound is 3.5-5 mol / L;

[0027] Preferably, the soaking time is 15-35 hours, the drying temperature is 70-90° C., and the drying time is 60-85 hours.

[0028] In a third aspect, the present invention provides the use of any of the solar-driven high-strength atmospheric water-collecting composite materials in the foregoing embodiments or the solar-driven high-strength atmospheric water-collecting composite materials prepared by any of the preparation methods in the foregoing embodiments in sand consolidation or ecological layer construction in arid areas.

[0029] The present invention has the following beneficial effects: by loading hygroscopic compounds on a gel substrate containing MXene, chitosan and polyacrylamide, the introduced MXene can be used as a photothermal component to give the hydrogel good photothermal conversion performance, relying only on solar energy to decompose and adsorb water without consuming energy; the prepared composite hydrogel material not only has larger pores, but also has very ideal strength and toughness, which is conducive to further broadening its application field, such as for sand solidification, for construction of ecological layers in arid areas, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 This is a physical picture of the preparation process of PAM-CS-MXene-LiCl hydrogel material;

[0032] Figure 2 The scanning electron microscope images of PAM-CS-MXene and PAM-CS-MXene-LiCl prepared in Example 1;

[0033] Figure 3 Dynamic contact angle test results for PAM-CS-MXene;

[0034] Figure 4 The results of UV-visible-near infrared spectroscopy testing of the materials prepared in Example 1 and the comparative example are shown in FIG.

[0035] Figure 5 The mechanical properties test results of the materials prepared in Example 1 and the comparative example are shown in FIG.

[0036] Figure 6 This is a graph showing the test results of the hygroscopic properties of the material PAM-CS-MXene-LiCl prepared in Example 1;

[0037] Figure 7 The moisture absorption isotherms of PAM-CS-MXene matrix and PAM-CS-MXene-LiCl aerogel after loading LiCl under different humidity conditions;

[0038] Figure 8 A comparison chart of the moisture absorption capacity of the material of the present invention and atmospheric water-collecting composite materials reported by other research institutes;

[0039] Fig. 9 The surface temperature of PAM-CS-MXene-LiCl under different light intensities and the 2 Surface temperature comparison chart under illumination;

[0040] Fig.10 Thermal images of PAM-CS-MXene-LiCl after irradiation for 180 min under different light intensities;

[0041] Fig.11 This is a graph showing the release performance test results of PAM-CS-MXene-LiCl prepared in Example 1;

[0042] Fig.12 This is a graph showing the cycle durability test results of PAM-CS-MXene-LiCl prepared in Test Example 1;

[0043] Fig.13 Schematic diagram of moisture absorption and release test for outdoor testing of PAM-CS-MXene-LiCl prepared in Test Example 1;

[0044] Fig.14 This is a moisture absorption result diagram of the outdoor test of PAM-CS-MXene-LiCl prepared in Test Example 1;

[0045] Fig.15 A graph showing the water quality test results collected for Example PAM-CS-MXene-LiCl;

[0046] Fig.16 This is a comparison chart of the hygroscopic properties of the products obtained from Example PAM-CS-MXene-LiCl and PAM-CS-PPy-LiCl in Comparative Example 2. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0048] The embodiment of the present invention provides a method for preparing a solar-driven high-strength atmospheric water-collecting composite material, comprising:

[0049] S1. Preparation of gel substrate

[0050] A gel substrate containing MXene, chitosan (CS) and polyacrylamide was prepared, and acrylamide monomer, MXene and chitosan were used as raw materials to prepare a hydrogel material through the polymerization of acrylamide monomer (AM).

[0051] Specifically, chitosan and acrylamide monomers are commercially available raw materials, and MXene is a commercially available two-dimensional transition metal carbide, nitride or carbonitride in the form of a dispersion with a concentration of 5 mg / mL and a model number of Ti3C2T x , single layer size 500-2000nm, purchased from Xinxin Technology Co., Ltd.

[0052] It should be noted that MXene, as a new type of two-dimensional titanium carbide nanomaterial, has the advantages of excellent electrical conductivity, good self-lubricating properties, large specific surface area, good water dispersibility and high photothermal conversion efficiency. It is usually used in energy storage, electromagnetic shielding, lubrication, antibacterial, catalysis and other fields. In recent years, it has also shown great application potential in the field of solar water vapor conversion and is one of the materials with the highest photothermal water vapor conversion efficiency reported so far. However, there has been no report on the photoresponsive application of atmospheric water harvesting based on MXene. Chitosan (CS) is the only alkaline polysaccharide with inherent biocompatibility and biodegradability, and has a rigid chain property that can enhance the mechanical strength of hydrogels.

[0053] In some embodiments, the preparation process of the gel substrate includes: mixing and dissolving chitosan, MXene and acrylamide monomers, performing a high temperature reaction in the presence of a crosslinker and an initiator to form a hydrogel, swelling the hydrogel, and freeze drying the hydrogel; the high temperature reaction temperature is 60-80°C, and the reaction time is 1-3 hours. Due to the introduction of chitosan, the reaction needs to be catalyzed at high temperature to form a uniform hydrogel, and no catalyst needs to be introduced.

[0054] Specifically, the reaction temperature can be 60°C, 70°C, 80°C, etc., and the reaction time can be 1 h, 2 h, 3 h, etc.

[0055] In some embodiments, chitosan is dissolved in an aqueous acetic acid solution to obtain a chitosan aqueous solution, the chitosan aqueous solution is mixed with a MXene dispersion to obtain a mixed solution, the mixed solution is mixed and dissolved with an acrylamide monomer, and then sequentially mixed with a cross-linking agent and an initiator and reacted at high temperature to form a hydrogel, the hydrogel is allowed to stand for 8-24 hours (such as 8 hours, 10 hours, 15 hours, 20 hours, 24 hours, etc.) and then washed with water, and then the washed hydrogel is immersed in water for swelling, and freeze-dried after freezing and setting. By controlling the addition method of the raw materials, the uniformity of the raw material mixing is improved, and after the reaction is completed, the structure of the hydrogel is more stable after being allowed to stand, and after washing with water to remove the unreacted monomers, water is allowed to enter the pores through immersion, and the water is absorbed and expanded, and the pores are opened to achieve the effect of full swelling. The swollen hydrogel is frozen and set, and then freeze-dried to remove moisture, such as Figure 1 Shown are, in sequence, the synthesized hydrogel, the swollen hydrogel, and the freeze-dried product.

[0056] Similarly, the crosslinking agent and initiator can also be dissolved in a small amount of water before being added to promote rapid and uniform mixing of the raw materials.

[0057] The inventors optimized the dosage of raw materials. The concentration of MXene in the mixed solution is 1-3 mg / mL, and the mass ratio of MXene to acrylamide monomer is 1:45-55. The volume fraction of acetic acid in the raw material acetic acid aqueous solution is controlled to be 2-3%, the concentration of MXene dispersion is 4-6 mg / mL, and the amount of acetic acid aqueous solution is used to control the mass fraction of chitosan in the chitosan aqueous solution to be 1-3%. By precisely controlling the concentration and dosage of raw materials in the hydrogel preparation process, the porosity effect and strength of the hydrogel are improved.

[0058] Specifically, the volume fraction of the raw material acetic acid aqueous solution used can be 2%, 2.5%, 3%, etc.; the mass fraction of chitosan in the chitosan aqueous solution can be 1%, 2%, 3%, etc. The concentration of the raw material MXene dispersion used can be 4 mg / mL, 5 mg / mL, 6 mg / mL, etc., but is not limited thereto, and commercially available raw materials can be used, and the concentration of MXene in the configured mixed solution can be controlled.

[0059] Specifically, the concentration of MXene in the mixed solution can be 1 mg / mL, 2 mg / mL, 3 mg / mL, etc., and the mass ratio of MXene to acrylamide monomer can be 1:45, 1:50, 1:55, etc.

[0060] Furthermore, the soaking time during swelling is 60-85 hours, and the water is replaced every 6-10 hours during the soaking process. The soaking process can further remove unreacted monomers, and the removal effect of impurities can be further improved by changing the water; during the soaking process, water can fully enter the pores to make them swell. Specifically, the soaking time is relatively long, and can be 60 hours, 65 hours, 70 hours, 75 hours, 80 hours, 85 hours, etc., and the interval time for changing the water can be 6 hours, 8 hours, 10 hours, etc.

[0061] Furthermore, the freezing setting time is 8-20 hours, such as 8 hours, 10 hours, 15 hours, 20 hours, etc., which can be carried out in a refrigerator. The freeze drying time is 60-85 hours to fully remove moisture, specifically 60 hours, 65 hours, 70 hours, 75 hours, 80 hours, 85 hours, etc., and the freeze drying temperature can be -30°C--40°C.

[0062] In some embodiments, the crosslinking agent is selected from at least one of N,N-methylenebisacrylamide (MBA), divinylbenzene and diisocyanate; the initiator is selected from at least one of potassium persulfate (KPS) and ammonium persulfate (APS), and the above raw materials are all suitable for the reaction system of the embodiment of the present invention, and any one or more of the above can be selected. The mass ratio of the crosslinking agent to the acrylamide monomer is 0.5-0.7:100, such as 0.5:100, 0.6:100, 0.7:100, etc.; the mass ratio of the initiator to the acrylamide monomer can be 3-5:100, 3:100, 4:100, 5:100, etc.

[0063] In some embodiments, before adding the crosslinking agent and the initiator, an inert gas is introduced into the system to remove oxygen in the system to prevent the presence of oxygen from affecting the polymerization reaction.

[0064] S2, Loading hygroscopic compounds

[0065] The hygroscopic compound is loaded on the gel substrate so that the hygroscopic compound is loaded on the surface and pores of the gel substrate. The loading method is not limited and can be a soaking method.

[0066] In some embodiments, the hygroscopic compound is selected from at least one of LiCl, CaCl2, MgSO4 and CuSO4, and can be a mixture of one or more thereof, preferably LiCl. The hygroscopic effect of the product prepared by using LiCl as the hygroscopic compound is more ideal.

[0067] In some embodiments, the process of loading the hygroscopic compound on the gel substrate includes: soaking the obtained gel substrate in an aqueous solution formed by the hygroscopic compound, taking it out and drying it. The hygroscopic compound such as LiCl is attached to the surface and pores of the gel by soaking, and the water is removed by drying.

[0068] In some embodiments, the concentration of the aqueous solution of the hygroscopic compound is 3.5-5 mol / L. Since the introduction of chitosan will affect the size of the pores to a certain extent, a higher concentration of solution is required for immersion to ensure the loading amount of materials such as LiCl. Specifically, the concentration of the aqueous solution of the hygroscopic compound can be 3.5 mol / L, 4.0 mol / L, 4.5 mol / L, 5.0 mol / L, etc.

[0069] Furthermore, the soaking time in the aqueous solution of the hygroscopic compound is 15-35 hours, the drying temperature after soaking is 70-90°C, and the drying time is 60-85 hours. The soaking time can be 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, etc. The drying temperature can be 70°C, 80°C, 90°C, etc., and the drying time can be 60 hours, 65 hours, 70 hours, 75 hours, 80 hours, 85 hours, etc.

[0070] The embodiment of the present invention provides a solar-driven high-strength atmospheric water-collecting composite material, including a gel substrate, wherein hygroscopic compounds are loaded in the pores and surface of the gel substrate; wherein the gel substrate contains MXene, chitosan and polyacrylamide. The solar-driven high-strength atmospheric water-collecting composite material can be prepared by the above-mentioned preparation method, and the obtained material has the characteristics of solar-driven and high-strength, and can be used in sand solidification.

[0071] In some embodiments, the loading amount of the hygroscopic compound is 3-5.2 g / g (such as 3.0 g / g, 3.5 g / g, 4.0 g / g, 4.5 g / g, 5.0 g / g, 5.2 g / g, etc.); preferably 3-4 g / g; preferably, in the gel matrix, the mass ratio of MXene, chitosan and polyacrylamide is 1:5-7:45-55 (1:5:45, 1:5.8-6.2:48-52, 1:7:55, etc.); preferably 1:5.8-6.2:48-52.

[0072] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0073] Example 1

[0074] This embodiment provides a method for preparing a solar-driven high-strength atmospheric water-collecting composite material, the steps of which are as follows:

[0075] Weigh 2g chitosan (CS) and dissolve it in 100mL acetic acid solution (volume fraction of 2.5%) to prepare CS aqueous solution (w = 2%); take 2mL of MXene dispersion with a concentration of 5mg / mL in a glass bottle, add 3mL CS aqueous solution and ultrasonicate for 1h to uniformly disperse MXene to obtain a mixed solution; weigh 0.5g acrylamide (AM) and add it to the mixed solution and ultrasonicate for 1min to fully dissolve the AM monomer, and then continuously introduce nitrogen into the solution to remove oxygen in the water. After the nitrogen blowing is completed, 0.8mL of 3.8mg / mL crosslinker MBA aqueous solution and 0.4mL of 50mg / mL initiator KPS aqueous solution prepared in advance are quickly added in sequence, magnetic stirring is followed by ultrasonic treatment for 2min, reaction is carried out at 70℃ for 2h to form a gel, and standing overnight (about 12h) to obtain PAM-MXene hydrogel, which is marked as PAM-CS-MXene. The PAM-CS-MXene hydrogel was rinsed with a large amount of deionized water to remove unreacted monomers and soaked for 72 hours, with the water changed every 8 hours to allow it to swell fully. It was placed in a refrigerator for 12 hours and then freeze-dried for 72 hours.

[0076] (2) The freeze-dried aerogel was immersed in 10 mL of 4 mol / mL LiCl aqueous solution for 24 h and then placed in a drying oven at 80 °C for 72 h and labeled as PAM-CS-MXene-LiCl.

[0077] Example 2

[0078] This embodiment provides a method for preparing a solar-driven high-strength atmospheric water-collecting composite material, the steps of which are as follows:

[0079] Weigh 2g chitosan (CS) and dissolve it in 200mL acetic acid solution (volume fraction is 2%) to prepare CS aqueous solution (w=1%); take 2mL of MXene dispersion with a concentration of 4mg / mL in a glass bottle, add 6mL CS aqueous solution and ultrasonicate for 1h to uniformly disperse MXene to obtain a mixed solution (MXene concentration is 1mg / mL); weigh 0.32g acrylamide (AM) and add it to the mixed solution and ultrasonicate for 1min to fully dissolve the AM monomer, and then continuously introduce nitrogen into the solution to remove oxygen in the water. After the nitrogen blowing is completed, 0.4mL of 3.8mg / mL crosslinker MBA aqueous solution and 0.2mL of 50mg / mL initiator KPS aqueous solution prepared in advance are quickly added in sequence, magnetic stirring is followed by ultrasonic treatment for 2min, reaction is carried out at 60℃ for 3h to form a gel, and standing overnight (about 8h) to obtain PAM-MXene hydrogel, which is marked as PAM-CS-MXene. The PAM-CS-MXene hydrogel was rinsed with a large amount of deionized water to remove unreacted monomers, and then soaked for 60 hours, with the water changed every 6 hours to allow it to swell fully. After being placed in a refrigerator for 8 hours, it was freeze-dried for 60 hours.

[0080] (2) The freeze-dried aerogel was immersed in 10 mL of 3.5 mol / mL LiCl aqueous solution for 15 h and then placed in a drying oven at 70 °C for 85 h and labeled as PAM-CS-MXene-LiCl.

[0081] Example 3

[0082] This embodiment provides a method for preparing a solar-driven high-strength atmospheric water-collecting composite material, the steps of which are as follows:

[0083] Weigh 3g chitosan (CS) and dissolve it in 100mL acetic acid solution (volume fraction is 3%) to prepare CS aqueous solution (w=3%); take 2mL of MXene dispersion with a concentration of 6mg / mL in a glass bottle, add 2mL CS aqueous solution and ultrasonicate for 1h to uniformly disperse MXene to obtain a mixed solution (MXene concentration is 3mg / mL); weigh 0.72g acrylamide (AM) and add it to the mixed solution and ultrasonicate for 1min to fully dissolve the AM monomer, and then continuously introduce nitrogen into the solution to remove oxygen in the water. After the nitrogen blowing is completed, 1.3mL of 3.8mg / mL crosslinker MBA aqueous solution and 0.7mL of 50mg / mL initiator KPS aqueous solution prepared in advance are quickly added in sequence, magnetic stirring is followed by ultrasonic treatment for 2min, reaction is carried out at 80℃ for 1h to form a gel, and standing for 24h to obtain PAM-MXene hydrogel, which is marked as PAM-CS-MXene. The PAM-CS-MXene hydrogel was rinsed with a large amount of deionized water to remove unreacted monomers and soaked for 85 hours, with the water changed every 10 hours to allow it to swell fully. It was placed in a refrigerator for 20 hours and then freeze-dried for 85 hours.

[0084] (2) The freeze-dried aerogel was immersed in 10 mL of 5 mol / mL LiCl aqueous solution for 35 h and then placed in a 90 °C drying oven for 60 h and labeled as PAM-CS-MXene-LiCl.

[0085] Comparative Example 1

[0086] The only difference from Example 1 is that CS is not added during the preparation process.

[0087] Comparative Example 2

[0088] The only difference from Example 1 is that MXene is replaced by polypyrrole (PPy).

[0089] Test Example 1

[0090] The scanning electron microscopy image of the PAM-CS-MXene matrix prepared in Test Example 1 is as follows: Figure 2As shown, from top to bottom are PAM-CS-MXene and PAM-CS-MXene-LiCl.

[0091] It can be seen that the PAM-CS-MXene matrix presents a dense porous morphology with interconnected pore channels.

[0092] Test Example 2

[0093] The dynamic contact angle test of freeze-dried PAM-CS-MXene was carried out, and the results are as follows: Figure 3 shown.

[0094] It can be seen that the contact angle of the PAM-CS-MXene surface is 0° at 100s, and the contact angle is 86.72° at the moment of contact with the droplet, which proves that the hydrophilicity of the matrix is ​​excellent.

[0095] Test Example 3

[0096] The PAM-CS-MXene prepared in Example 1 was subjected to UV-visible-near infrared spectroscopy test and compared with Comparative Example 1. The results are as follows: Figure 4 shown.

[0097] As shown in the UV-vis-NIR spectrum, the PAM-CS-MXene hydrogel matrix has strong absorption intensity in the range of 240nm-1400nm, and has significant light absorption intensity compared with the matrix without MXene in the entire spectrum range. This shows that the introduction of MXene allows the solar energy falling on the hydrogel to be collected and then converted into light and heat, providing sufficient energy for the release of adsorbed water.

[0098] Test Example 4

[0099] The tensile strength and elongation at break of the PAM-CS-MXene hydrogel (water content 50%) prepared in Example 1 were tested. The results are as follows: Figure 5 shown.

[0100] from Figure 5 It can be seen that the tensile strength and elongation at break of PAM-CS-MXene hydrogel are as high as 1.303MPa and 1013.137%, respectively. The tensile strength and elongation at break of PAM-MXene hydrogel without CS are as high as 0.445MPa and 1090.13%, respectively.

[0101] Test Example 5

[0102] The hygroscopic properties of PAM-CS-MXene-LiCl prepared in Example 1 were tested, and the results were as follows: Figure 6-Figure 10 shown.

[0103] The results show that under the conditions of relative humidity of 30%, 40%, 60%, 80%, 90% and 25°C, the corresponding adsorption rates of PAM-CS-MXene-LiCl when it reaches saturation are 5.00 g / min and 5.00 g / min, respectively. -1 , 3.35gg -1 , 1.84gg -1 , 1.36gg -1 , 0.78gg -1 .

[0104] Test Example 6

[0105] The release performance of PAM-CS-MXene-LiCl prepared in Example 1 was tested, and the results were as follows: Fig.11 shown.

[0106] from Fig.11 It can be seen that the PAM-CS-LiCl hydrogel without MXene is 2 Under the irradiation of 0.5 kW / m, the surface temperature of the PAM-CS-MXene-LiCl hydrogel slowly increased from room temperature to 37.1 °C within 180 min, while the temperature of the PAM-CS-MXene-LiCl hydrogel rapidly increased to 44.3 °C within 10 min and reached 57.6 °C in 180 min under the same conditions. 2 , 1kW / m 2 , 1.5kW / m 2 , 2kW / m 2 Under the light intensity of 1kW / m, the surface temperature can reach 43℃, 57.6℃, 74.7℃, and 82.8℃ respectively within 180min. Under the irradiation of different light intensities for 4h, PAM-CS-MXene-LiCl can release 58.28%, 81.56%, 90.53%, and 94.17% of adsorbed water respectively, while PAM-CS-LiCl can release 50.3% of adsorbed water under the light intensity of 1kW / m 2 Only less than 50% of the adsorbed water can be released under low temperature, highlighting the excellent water release performance of the composite hydrogel.

[0107] Test Example 7

[0108] The cycle durability of PAM-CS-MXene-LiCl prepared in Example 1 was tested, and the results were as follows: Fig.12 shown.

[0109] The PAM-CS-MXene-LiCl gel was subjected to five adsorption-desorption durability cycle experiments. The results showed that similar water absorption and residual amounts appeared in each cycle without obvious decrease, indicating high reusability.

[0110] Test Example 8

[0111] The PAM-CS-MXene-LiCl prepared in Example 1 was tested outdoors. Fig.13 and Fig.14 shown.

[0112] On a night with an average temperature of 30.27°C and a relative humidity of 62.2%, 8.39 g of PAM-CS-MXene-LiCl aerogel discs were fully exposed to the air from 7 pm to 8 am the next day, absorbing 14.99 g of atmospheric water with a water absorption rate of 1.79 g / g.

[0113] The release experiment lasted from 9:00 a.m. to 6:00 p.m. (average temperature was 36.48°C, light intensity was 0.775 kW / m 2 ), the aerogel was placed in a closed water collection device and 7.74 g of water was collected, with a water collection rate of 0.9223 L / kg.

[0114] Collected water quality testing: By using inductively coupled plasma mass spectrometer (ICP-MS) and ion chromatograph, the concentration of lithium ions and chloride ions in the collected water can be detected to avoid LiCl leakage, such as Fig.15 The results show that the lithium ion concentration is 3.3664 mg L -1 . The chloride ion concentration is 29.9806 mg L -1 , which is lower than the chloride concentration limit for drinking water set by the World Health Organization (250 mg L -1 ). This indicates that the collected water is safe and meets drinking water requirements.

[0115] Test Example 9

[0116] The hygroscopic properties of the products obtained from the test example PAM-CS-MXene-LiCl and the PAM-CS-PPy-LiCl in comparative example 2 are compared as shown in FIG. Fig.16 As shown. Test conditions: 90% humidity and 25°C. It can be seen that the moisture absorption performance of PAM-CS-MXene-LiCl is significantly better.

[0117] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A solar-driven high-strength atmospheric water-collecting composite material, characterized in that: It includes a gel substrate, wherein the pores and the surface of the gel substrate are loaded with a hygroscopic compound; Wherein, the gel substrate contains MXene, chitosan and polyacrylamide; The loading amount of the hygroscopic compound is 3-4 g / g, and the mass ratio of MXene, chitosan and polyacrylamide in the gel substrate is 1:5.8-6.2:48-52; The hygroscopic compound is LiCl.

2. A method for preparing the solar-driven high-strength atmospheric water-collecting composite material according to claim 1, characterized in that: include: The gel substrate containing MXene, chitosan and polyacrylamide is prepared, and the hygroscopic compound is loaded on the gel substrate.

3. The preparation method according to claim 2, characterized in that: The preparation process of the gel substrate includes: mixing and dissolving chitosan, MXene and acrylamide monomers, reacting at high temperature in the presence of a cross-linking agent and an initiator to form a hydrogel, and swelling and freeze-drying the hydrogel.

4. The preparation method according to claim 3, characterized in that: The high temperature reaction has a reaction temperature of 60-80° C. and a reaction time of 1-3 hours.

5. The preparation method according to claim 3, characterized in that: Chitosan is dissolved in an acetic acid aqueous solution to obtain a chitosan aqueous solution, the chitosan aqueous solution is mixed with a MXene dispersion to obtain a mixed solution, the mixed solution is mixed and dissolved with an acrylamide monomer, and then sequentially mixed with the cross-linking agent and the initiator and reacted at high temperature to form a hydrogel, the hydrogel is allowed to stand for 8-24 hours and then washed with water, and then the washed hydrogel is immersed in water for swelling, and freeze-dried after being frozen and fixed.

6. The preparation method according to claim 5, characterized in that: The soaking time is 60-85 hours, and the water is replaced every 6-10 hours during the soaking process.

7. The preparation method according to claim 5, characterized in that: The freezing setting time is 8-20 hours, and the freeze drying time is 60-85 hours.

8. The preparation method according to claim 5, characterized in that: The concentration of MXene in the mixed solution is 1-3 mg / mL, and the mass ratio of MXene to acrylamide monomer is 1:45-55.

9. The preparation method according to claim 8, characterized in that: When the acetic acid aqueous solution is prepared, the volume fraction of acetic acid is controlled to be 2-3%, the mass fraction of chitosan in the chitosan aqueous solution is 1-3%; and the concentration of the MXene dispersion is 4-6 mg / mL.

10. The preparation method according to claim 5, characterized in that: The crosslinking agent is selected from at least one of N,N-methylenebisacrylamide, divinylbenzene and diisocyanate.

11. The preparation method according to claim 5, characterized in that: The initiator is selected from at least one of potassium persulfate and ammonium persulfate.

12. The preparation method according to claim 5, characterized in that: The mass ratio of the crosslinking agent to the acrylamide monomer is 0.5-0.7:100, and the mass ratio of the initiator to the acrylamide monomer is 3-5:

100.

13. The preparation method according to claim 5, characterized in that: Before adding the crosslinking agent and the initiator, an inert gas is introduced into the system to remove oxygen in the system.

14. The preparation method according to any one of claims 2 to 5, characterized in that: The process of loading the hygroscopic compound on the gel substrate comprises: immersing the obtained gel substrate in an aqueous solution formed by the hygroscopic compound, taking it out and drying it; wherein the concentration of the aqueous solution of the hygroscopic compound is 3.5-5 mol / L.

15. The preparation method according to claim 14, characterized in that: The soaking time is 15-35h, the drying temperature is 70-90℃, and the drying time is 60-85h.

16. Use of the solar-driven high-strength atmospheric water-collecting composite material according to claim 1 or the solar-driven high-strength atmospheric water-collecting composite material prepared by the preparation method according to any one of claims 2 to 15 in sand consolidation or ecological layer construction in arid areas.

Citation Information

Patent Citations

  • Self-hygroscopic hydrogel, preparation method and thermal management method based on self-hygroscopic hydrogel

    CN109943002A

  • MXene hydrogel with high strength, electrical conductivity and high and low temperature resistance, and preparation method and application thereof

    CN110922611A

  • Water vapor harvesting materials and devices

    CN112135676A